A Mixed Effect Analysis of Head Impact Accelerations During Rugby Head Impacts Under Different Gameplay Conditions - Danyon Stitt; Nicole Spriggs; Stefan Henley; Keith Alexander; Nick Draper; Natalia Kabaliuk (Annals of Biomedical Engineering, 2026)
Purpose Exposure to head acceleration events in rugby can lead to both physical and mental health problems, even without a diagnosed traumatic brain injury. This study aimed to explore relationships between gameplay head impact conditions and head acceleration metrics experienced by rugby players. Methods Using head impact kinematic data from two high school rugby union teams in New Zealand (one male and one female), linear mixed-effect models identified significant trends between gameplay techniques, head impact mechanisms, and the resulting linear and rotational peak accelerations and injury criteria. Results Head impacts to bony body regions, crushing head impacts, and head impacts to the ground produced the highest linear and rotational acceleration metrics. Impacts between the head and the ball also resulted in higher rotational accelerations than head impacts with the hip and soft body regions. Indirect head acceleration events and head-to-tackle pad impacts resulted in the lowest acceleration metrics. Males showed lower acceleration metrics during training drills, mauls, and scrums than females. Impacts to the chin resulted in the highest peak accelerations, followed by impacts to the rear of the head, with impacts to the front, top, or side of the head resulting in the lowest acceleration metrics. Indirect head acceleration events resulting in flexion/extension or lateral rotational motion induced the highest acceleration metrics. The tackling technique had limited effect on the acceleration metrics of the tackler, with tackles made to the torso/hip region and upper leg region, both with the head beside the tackle location, resulting in the highest peak accelerations. Conclusion This analysis could indicate gameplay events that require further investigation to improve player safety without employing protective equipment.

Assessing the Efficacy of GameBreaker Softshell Headgear in Reducing Peak Head Kinematics - Annette G. Heward-Swale; George Stilwell; Elena Moltchanova; Nick Draper; Natalia Kabaliuk (Annals of Biomedical Engineering, 2026)
Purpose This study evaluates the impact-attenuation of two softshell headgear models, GameBreaker-Pro and GameBreaker-Prototype, in controlled drop tests. These models were selected to assess the effect of thickness, given the 12 mm thickness constraint specified under World Rugby Law 4 Trial regulations for which limited justification exists. Methods Drop tests were conducted using a Hybrid III headform and neck, from heights of 15, 30, 45, and 60 cm onto a flat Modular Elastomer Programmer (MEP) surface. Impacts were delivered across five orientations; forehead, front boss, rear boss, rear, and side, to simulate a range of plausible on-field rugby impact scenarios. Peak linear acceleration (PLA), peak rotational acceleration (PRA), and peak rotational velocity (PRV) were measured across four headgear conditions: GameBreaker-Pro, GameBreaker-Prototype, NPro (World Rugby Law 4 Trial approved), and a no-headgear baseline. Results All headgear models demonstrated reductions in impact kinematics relative to the no-headgear baseline. GameBreaker-Pro yielded the highest composite reductions (peak accelerations across all orientations), lowering PLA by 32.3% and PRA by 43.4%, followed closely by GameBreaker-Prototype with reductions of 30.4% and 42.2%, respectively. Both GameBreaker models showed consistent attenuation across drop heights and orientations, with particularly strong performance in the side (reductions of 43.5% and 37.1% in PLA, 59.1% and 54.3% in PRA). Conclusion These findings demonstrate that softshell headgear can reduce head impact severity across diverse conditions. This underscores the need for ongoing refinement of headgear design and regulatory standards to better safeguard athletes from repeated intensive head impacts.

The Impact of Drop Test Conditions on Brain Strain Location and Severity: A Novel Approach Using a Deep Learning Model - George Stilwell; Danyon Stitt; Keith Alexander; Nick Draper; Natalia Kabaliuk (Annals of Biomedical Engineering, 2024)
In contact sports such as rugby, players are at risk of sustaining traumatic brain injuries (TBI) due to high-intensity head impacts that generate high linear and rotational accelerations of the head. Previous studies have established a clear link between high-intensity head impacts and brain strains that result in concussions. This study presents a novel approach to investigating the effect of a range of laboratory controlled drop test parameters on regional peak and mean maximum principal strain (MPS) predictions within the brain using a trained convolutional neural network (CNN). The CNN is publicly available at https://github.com/Jilab-biomechanics/CNN-brain-strains . The results of this study corroborate previous findings that impacts to the side of the head result in significantly higher regional MPS than forehead impacts. Forehead impacts tend to result in the lowest region-averaged MPS values for impacts where the surface angle was at 0° and 45°, while side impacts tend to result in higher regional peak and mean MPS. The absence of a neck in drop tests resulted in lower regional peak and mean MPS values. The results indicated that the relationship between drop test parameters and resulting regional peak and mean MPS predictions is complex. The study’s findings offer valuable insights into how deep learning models can be used to provide more detailed insights into how drop test conditions impact regional MPS. The novel approach used in this paper to predict brain strains can be applied in the development of better methods to reduce the brain strain resulting from head accelerations such as protective sports headgear.

Drop Test Kinematics Using Varied Impact Surfaces and Head/Neck Configurations for Rugby Headgear Testing - Danyon Stitt; Natalia Kabaliuk; Keith Alexander; Nick Draper (Annals of Biomedical Engineering, 2022)
World Rugby employs a specific drop test method to evaluate headgear performance, but almost all researchers use a different variation of this method. The aim of this study was, therefore, to quantify the differences between variations of the drop testing method using a Hybrid III headform and neck in the following impact setups: (1) headform only, with a flat steel impact surface, approximating the World Rugby method, (2 and 3) headform with and without a neck, respectively, onto a flat MEP pad impact surface, and (4) headform and neck, dropped onto an angled MEP pad impact surface. Each variation was subject to drop heights of 75–600 mm across three orientations (forehead, side, and rear boss). Comparisons were limited to the linear and rotational acceleration and rotational velocity for simplicity. Substantial differences in kinematic profile shape manifested between all drop test variations. Peak accelerations varied highly between variations, but the peak rotational velocities did not. Drop test variation also significantly changed the ratios of the peak kinematics to each other. This information can be compared to kinematic data from field head impacts and could inform more realistic impact testing methods for assessing headgear.

Potential of Soft-Shell Rugby Headgear to Mitigate Linear and Rotational Peak Accelerations - Danyon Stitt; Natalia Kabaliuk; Keith Alexander; Nick Draper (Annals of Biomedical Engineering, 2022)
Rugby union is a popular sport played across the world. The physical contact inherent in the game means that players are at increased risk of concussive injury. In 2019, World Rugby created a new category of permitted headgear under Law 4 as a medical device. This established a pathway for headgear designed to reduce peak accelerations to be worn in matches. Investigations of the potential of soft-shelled protective headgear to reduce head impact accelerations have been mostly limited to the analysis of linear kinematics. However rotational head impact accelerations have long been implicated as far more injurious. The aim of this study, therefore, was to assess the linear and rotational acceleration reduction brought about by soft-shelled rugby headgear. A Hybrid III headform and neck were dropped onto a modular elastomer programmer impact surface, impacting at four different velocities (1.7–3.4 m/s) in five different impact orientations. Impact surface angles were 0°, 30°, and 45°. Peak linear and rotational accelerations, PLA and PRA respectively, were recorded. All headgear significantly reduced PLAs and PRAs when compared to a no headgear scenario. The new generation, headgear reduced all measures significantly more than the older generation of headgear. Impact locations offset from the center of mass of the headform resulted in the highest PRAs measured. As the impact surface angle increased, both PLAs and PRAs decreased. The study demonstrated that headgear tested lowered PLAs by up to 50%, and PRAs by up to 60% compared to the bare headform. Our data suggest that new generation headgear could make a difference on the field in reducing injurious impact accelerations in a collision.

Validity of the Polar V800 heart rate monitor to measure RR intervals at rest - David Giles; Nick Draper; William Neil (European Journal of Applied Physiology, 2016)

Effects of resistance training combined with vascular occlusion or hypoxia on neuromuscular function in athletes - Apiwan Manimmanakorn; Nuttaset Manimmanakorn; Robert Taylor; Nick Draper; Francois Billaut; Jeremy P. Shearman; Michael J. Hamlin (European Journal of Applied Physiology, 2013)

The influence of sampling site and assay method on lactate concentration in response to rock climbing - Nick Draper; Simon Brent; Beverley Hale; Ian Coleman (European Journal of Applied Physiology, 2006)